TYPES AND ABUNDANCE OF MARINE DEBRIS IN THE NORTH COASTAL REGION OF BENGKALIS ISLAND, RIAU - Sianturi, Desi Deria; Amin, Bintal; Zulkifli, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Marine debris is a threat that is currently the biggest problem in the world due to the impact that trash can have on the survival of aquatic biota. This research was conducted to analyze the type and abundance and differences in the abundance of marine debris found in the northern coastal area of Bengkalis Island, Riau Province, which is assumed to be a location with the potential for accumulation of waste that could threaten the life of biota in the waters. The method used is the survey method, namely collecting data, documentation, and observation. Waste collection is carried out at three stations by determining the research location along 100 m and dividing each 20 m so there are five transects. Then, on each transect, a plot with a size of 5x5 m was made. Then, collect every type of waste contained in the plot. The results showed that plastic waste was the most common type (62%), while wood was the least found (1%). The abundance of waste on weekends is higher than on weekdays. The difference in the abundance of waste between stations was not significantly different, while the difference between the abundance of time (weekdays and weekends) was significantly different.